Detection of H. pylori DNA in gastric epithelial cells by in situ hybridization - Lu, Xin-Liang (World J Gastroenterol, 2002)
AIM: To investigate the presence of H. pylori DNA within gastric epithelial cells in patients with H. pylori infection and its possible carcinogenic mechanism. METHODS: Total 112 patients, with pathologically confirmed chronic superficial gastritis, chronic atrophic gastritis, intestinal metaplasia, atypical hyperplasia or gastric cancer were studied. Among them, 28 were H. pylori negative and 84 H. pylori positive. H. pylori DNA in gastric epithelial cells was detected by GenPoint catalyzed signal amplification system for in situhybridization. RESULTS: In the H. pylori positive group, zero out of 24 chronic superficial gastritis (0.0%), four out of 25 precancerous changes (16.0%) and thirteen out of 35 gastric cancers (37.1%) showed H. pylori DNA in the nucleus of gastric epithelial cells, the positive rates of H. pylori DNA in the nucleus of gastric epithelial cells were progressively increased in chronic superficial gastritis, precancerous changes and gastric cancer groups (χ² = 12.56, P = 0.002); One out of 24 chronic superficial gastritis (4.2%), eleven out of 25 precancerous changes (44.0%) and thirteen out of 35 gastric cancers (37.1%) showed H. pylori DNA in the cytoplasm of gastric epithelial cells (χ² = 10.86, P = 0.004). In the H. pylori negative group, only one patient with gastric cancer was found H. pylori DNA in the nucleus of gastric epithelial cells; Only two patients, one patient with precancerous changes and another with gastric cancer, showed H. pylori DNA in the cytoplasm of gastric epithelial cells. Furthermore, H. pylori DNA must have been in the cytoplasm as long as it existed in the nucleus of gastric epithelial cells. CONCLUSION: H. pylori DNA exists both in the nucleus and the cytoplasm of gastric epithelial cells in patients with H. pylori infections. The pathological progression from chronic superficial gastritis, precancerous changes to gastric cancer is associated with higher positive rates of H. pylori DNA presence in the nucleus of gastric epithelial cells.